Kuat Tekan Dan Perubahan Berat Beton OPC Dan OPC POFA Dengan Menggunakan Air Gambut Sebagai Air Pencampur Di Lahan Gambut - Gustina Gultom; Ismediyanto Ismediyanto; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research study the compressive strength and mass loss of OPC concrete and concrete combine of OPC +10% palm oil fuel ash (POFA). The specimens cured in peat environment until 28 days. Compressive strength of concrete OPC G higher than OPC POFA G because reaction of pozzolanic make slowly calcium silicat. Weight changes showed OPC G until 28 days increased because acid can make expantions so volume of concrete increased. Concrete OPC G +10% POFA decreased because reaction pozzolanic can less acid for concrete.Keywords: Durability, OPC, POFA, peat environment.